MODEL-MODEL EVALUASI PEMBELAJARAN PAI (Model Pengukuran, Model Kesesuaian, Model Sistem dan Model Illuminatif) - Nurul Ilmi; Rodiah, Kamilatur (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2024)
Islamic religious education (PAI) also has an important role in forming students' spiritual values ​​and souls. Through the PAI learning process, it is hoped that students can gain a grip on daily life based on Islamic teachings, and become responsible individuals who are guided by the values ​​of the al-Quran and Sunnah. Various learning evaluation models are carried out with the aim of improving the quality of learning and increasing its effectiveness. Evaluation is an important part of the educational process, because it provides information about learning performance and helps in making decisions for future improvements. The PAI learning evaluation model must be prepared by combining an authentic assessment approach with learning characteristics in Islamic concepts. Evaluation of the achievement of cognitive, affective and psychomotor competencies is directed at achieving a balance between aspects of thought and action. There are 4 classifications of evaluation models that have been classified by various researchers: 1. Measurement Model, 2. Congruence Model, 3. System Model, 4. Illuminative Model.